Delineating the molecular mechanisms of hippocampal neurotoxicity induced by chronic administration of synthetic cannabinoid AB-FUBINACA in mice - Ayman Alzu'bi (18192898) (2024)
Chronic use of synthetic cannabinoids (SCs) has been associated with cognitive and behavioural deficits and an increased risk of neuropsychiatric disorders. The underlying molecular and cellular mechanisms of the neurotoxic effects of long-term use of SCs have not been well investigated in the literature. Herein, we evaluated the in vivo effects of chronic administration of AB-FUBINACA on the hippocampus in mice. Our results revealed that the administration of AB-FUBINACA induced a significant impairment in recognition memory associated with histopathological changes in the hippocampus. These findings were found to be correlated with increased level of oxidative stress, neuroinflammation, and apoptosis markers, and reduced expression of brain-derived neurotrophic factor (BDNF), which plays an essential role in modulating synaptic plasticity integral for promoting learning and memory in the hippocampus. Additionally, we showed that AB-FUBINACA significantly decreased the expression of NR1, an important functional subunit of glutamate/NMDA receptors and closely implicated in the development of toxic psychosis. These findings shed light on the long-term neurotoxic effects of SCs on hippocampus and the underlying mechanisms of these effects. This study provided new targets for possible medical interventions to improve the treatment guidelines for SCs addiction. Other Information Published in: NeuroToxicology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.neuro.2024.05.009